Terbium(III) Luminescence-Based Assay for Esterase Activity - Hetrick, Kenton J. (Anal Chem, 2019)
Esterases catalyze the hydrolysis of esters to form a carboxylic acid and alcohol. These enzymes play a key role in both the detoxification of xenobiotic compounds and the metabolism of drugs and prodrugs. Numerous fluorogenic probes have been developed to monitor esterase activity. Most are based on an aromatic alcohol, and the others are based on an aromatic acid. These restrictions leave unexplored the specificity of esterases for aliphatic esters. Here, we report on the use of esters of thiopheneacetic acid coupled with the luminescence of terbium(III) as the basis for a continuous assay of esterase activity. This probe allows for wide variation of the alcohol moiety and the detection of its hydrolysis at sub-micromolar concentrations. The assay verifies steady-state kinetic parameters for catalysis by pig liver esterase from either initial rates or the integration of progress curves, and its utility is evident with unpurified esterases in bacterial and human cell lysates.